Rhinophrus Hsiao (Insecta: Hemiptera: Heteroptera: Miridae) from Thailand, with description of a new species - Andrzej Wolski; Tomohide Yasunaga (European Journal of Taxonomy)
Two little-known genera, Mimofulvius Schmitz, 1978 and Rhinophrus Hsiao, 1944, are reported from Thailand for the first time. A new species of Mimofulvius, M. castaneus sp. nov., is described, and the male of the type species of the genus, M. pentatomus Schmitz, 1978, is documented for the first time. A key to species of Mimofulvius is given. Habitus images of the adult of all treated species and illustrations of the male genitalic structures of M. castaneus and M. pentatomus are also provided. The female genitalia of Rhinophrus borneensis Hsiao, 1944 are documented for the first time. Scanning electron micrographs of selected structures of M. castaneus, M. pentatomus, and Rhinophrus borneensis are provided. The systematic position is also discussed for Mimofulvius and Rhinophrus.